Aqueous solution‐processed NiOx anode buffer layers applicable for polymer solar cells. Issue 4 (24th November 2016) - Yang, Weitao; Yu, Zhikai; Liu, Wenqing; Li, Chang‐Zhi; Chen, Hongzheng
ABSTRACT: A green and facile method has been developed for the room temperature and aqueous solution preparation of NiOx film as anode buffer layers for polymer solar cells (PSCs). The NiOx buffer layer is prepared simply by spin‐coating nickel acetylacetonate precursor‐based aqueous solution onto ITO substrate at room temperature in air. UV‐ozone post‐treatment promotes the formation of dipolar NiOOH species on the film surface, resulting in the anode buffer layer with suitable work function. PSCs have been fabricated with the device structure of ITO/NiOx /photoactive layer/PFN/Al. The power conversion efficiencies of the PSCs based on PTB7:PC71 BM blends (8.43%) and P3HT:PC71 BM blends (3.04%) with NiOx anode buffer layer are comparable to those with the commonly used PEDOT:PSS anode buffer layer. In addition, the devices made with NiOx buffer layer exhibit much better air stability than those with PEDOT:PSS. These results indicate that the water solution processed NiOx film at room temperature in air is a promising anode buffer layer for efficient and stable PSCs. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 747–753 Abstract : A facile and green method has been developed to fabricate NiOx anode buffer layer for polymer solar cells (PSCs) via water solution processing at room temperature in air. The PSC devices with NiOx anode buffer layer show comparable power conversion efficiency but better air stability than those with PEDOT:PSS buffer layer, indicating that the water solution processed NiOx film is a promising anode buffer layer for efficient and stable PSCs.